The Difficulties of Mastering Causative Verbs Attained By the 3rd Semester Students at University of Muhammadiyah Tangerang - Imtihan Hanim (ASIAN PUBLISHER, 2023)
The study is aim at analysing students’ problems when learning causative verbs in Advanced English Grammar Class. The participants come from the third semesters students. Ten students are chosen as a sampling. The qualitative study is chosen to gather the data related to the students’ problems in comprehending causative verbs. The researcher used an interview as a data collection. The questions are about problems, the causes of the problems, the strategies of overcoming their problems, the most difficult part of causative verbs and their perception on causative verbs. The findings show that most of them get confused at the beginning when they were not in a good concentration. Get is the most difficult form of causative verbs. Their perception about causative verbs was quite good to learn since they had big effort to comprehend it. Sometimes, they preferred to ask their friends to reexplain about the materials. However, less of them were preferred to ask the lecturer as their learning strategy.